2017
DOI: 10.1039/c7dt03380j
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium tricarbonyl complexes of AIE active tetraarylethylene ligands: tuning luminescence properties and HSA-specific binding

Abstract: The synthesis and photophysical properties of luminescent Re(i) tricarbonyl complexes prepared from bis(pyridyl)- and bis(quinolyl) tetraarylethylene (TAE) ligands are reported. Emission wavelengths of the complexes are influenced by structural variation in the tetraarylethylene ligands, and several complexes display aggregation-induced enhanced emission in aqueous solution. A Re(i) complex prepared from an indole-functionalized TAE ligand shows significant enhancement in its luminescence intensity accompanied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…The synthesis of TAE ligands employed in this study is shown in Scheme . The route used to construct ligands 6 – 8 is analogous to procedures we have previously reported for the preparation of related TAE derivatives . Briefly, dibromoalkene 5 was obtained upon treatment of bis(benzothiazol‐2‐yl)methanone ( 4 ) with CBr 4 and PPh 3 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The synthesis of TAE ligands employed in this study is shown in Scheme . The route used to construct ligands 6 – 8 is analogous to procedures we have previously reported for the preparation of related TAE derivatives . Briefly, dibromoalkene 5 was obtained upon treatment of bis(benzothiazol‐2‐yl)methanone ( 4 ) with CBr 4 and PPh 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The route used to construct ligands 6-8 is analogous to procedures we have previously reported for the preparation of related TAEd erivatives. [4] Briefly,d ibromoalkene 5 was obtained upon treatment of bis(benzothiazol-2-yl)methanone (4)w ith CBr 4 and PPh 3 .S ubsequent double Suzuki reaction of 5w ith aryl boronic acids or pinacol esters then afforded 6-8 in good yields.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations